The novel iron chelator, 2-pyridylcarboxaldehyde 2-thiophenecarboxyl hydrazone, reduces catecholamine-mediated myocardial toxicity - Mladĕnka, Premysl; Kalinowski, Danuta S; Haskova, Pavlína; Bobrovová, Zuzana; Hrdina, Radomír; Simůnek, Tomás; Nachtigal, Petr; Semecký, Vladimĺr; Vávrová, Jaroslava; Holeckova, Magdaléna; Palicka, Vladimir; Mazurová, Yvona; et al. (Chemical research in toxicology, 2009)
Iron (Fe) chelators are used clinically for the treatment of Fe overload disease. Iron also plays a role in the pathology of many other conditions, and these potentially include the cardiotoxicity induced by catecholamines such as isoprenaline (ISO). The current study examined the potential of Fe chelators to prevent ISO cardiotoxicity. This was done as like other catecholamines, ISO contains the classical catechol moiety that binds Fe and may form redox-active and cytotoxic Fe complexes. Studies in vitro used the cardiomyocyte cell line, H9c2, which was treated with ISO in the presence or absence of the chelator, desferrioxamine (DFO), or the lipophilic ligand, 2-pyridylcarboxaldehyde 2-thiophenecarboxyl hydrazone (PCTH). Both of these chelators were not cardiotoxic and significantly reduced ISO cardiotoxicity in vitro. However, PCTH was far more effective than DFO, with the latter showing activity only at a high, clinically unachievable concentration. Further studies in vitro showed that interaction of ISO with Fe(II)/(III) did not increase cytotoxic radical generation, suggesting that this mechanism was not involved. Studies in vivo were initiated using rats pretreated intravenously with DFO or PCTH before subcutaneous administration of ISO (100 mg/kg). DFO at a clinically used dose (50 mg/kg) failed to reduce catecholamine cardiotoxicity, while PCTH at an equimolar dose totally prevented catecholamine-induced mortality and reduced cardiotoxicity. This study demonstrates that PCTH reduced ISO-induced cardiotoxicity in vitro and in vivo, demonstrating that Fe plays a role, in part, in the pathology observed.
Keywords: Isoproterenol; Cell Line; Male; Catecholamines; Rats, Wistar; thiofeny; železo; Iron Chelating Agents; chelátory železa; mužské pohlaví; potkani Wistar; oxidace-redukce; krysa rodu Rattus; deferoxamin; katecholaminy; kardiomyocyty; Animals; Iron; zvířata; Rats; Myocytes, Cardiac; isoprenalin; buněčné linie; Thiophenes; Oxidation-Reduction; Deferoxamine